1999
DOI: 10.1007/s11743-999-0075-6
|View full text |Cite
|
Sign up to set email alerts
|

Clearning performance and foaming properties of lauroylamidopropylbetaine/nonionics mixed systems

Abstract: Lauroylamidopropylbetaine (LPB) has good cleaning and foaming performance with excellent low skin irritation. We have investigated the relationship between cleaning performance and foaming properties of aqueous solutions containing binary and ternary LPB/nonionic surfactant systems. Foaming properties were evaluated by observing dynamic surface tension and aqueous core thickness of a vertical foam film measured by Fourier transform infrared spectroscopy. The LPB/lauroyldiethanolamide (LDE) system has a positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
(13 reference statements)
0
7
0
5
Order By: Relevance
“…They found that both the monomers and micelles were able to penetrate into the epidermis [7]. One of the potential means of preventing these adverse effects is the addition of co-surfactants [18][19][20][21][22][23][24][25][26][27], hydrolyzed proteins [28][29][30] or polymers [30][31][32]. The action mechanisms of the additives involve an increase in micelle size or formation of appropriate complexes leading to a decreased concentration of free surfactant molecules in the solution [15,33].…”
Section: Introductionmentioning
confidence: 99%
“…They found that both the monomers and micelles were able to penetrate into the epidermis [7]. One of the potential means of preventing these adverse effects is the addition of co-surfactants [18][19][20][21][22][23][24][25][26][27], hydrolyzed proteins [28][29][30] or polymers [30][31][32]. The action mechanisms of the additives involve an increase in micelle size or formation of appropriate complexes leading to a decreased concentration of free surfactant molecules in the solution [15,33].…”
Section: Introductionmentioning
confidence: 99%
“…al. (1999) [17], a capacidade de remoção de detritos gordurosos de superfícies hidrofóbicas foi avaliada em triplicata, empregando soluções de tensoativos na concentração de 1%, em água destilada e dura (100 mM CaCO 3 ).…”
Section: Capacidade Detergenteunclassified
“…O substrato hidrofóbico utilizado pode ter composição química e tamanhos de partículas variados [51]. Tamura et. al.,(1999) [17], avaliaram a performance de limpeza de soluções contendo sistemas combinados de tensoativos sintéticos, e concluiu que o sistema lauroilamidopropilbetaína (LAPB)/ lauroildietanolamina (LDT) apresentou sinergismo positivo na atividade detergente.…”
Section: Capacidade Detergenteunclassified
“…Consequently, the addition of zwitterionic and/or nonionic surfactants to anionic surfactants is preferred. Amphoteric surfactants, such as betaines, which possess excellent detergency on oily residues and biodegradability, are used frequently in household detergents [20]. The cleaning of betaines with excellent temperature stability is much better when the nonionic surfactant is used with the amphoteric and can thicken the composition without using a thickener.…”
Section: Introductionmentioning
confidence: 99%